2010
DOI: 10.1111/j.1476-5381.2010.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting drug‐induced slowing of conduction and pro‐arrhythmia: identifying the ‘bad’ sodium current blockers

Abstract: Background and purpose:The regulatory guidelines (ICHS7B) for the identification of only drug-induced long QT and pro-arrhythmias have certain limitations. Experimental approach: Conduction time (CT) was measured in isolated Purkinje fibres, left ventricular perfused wedges and perfused hearts from rabbits, and sodium current was measured in Chinese hamster ovary cells, transfected with Nav1.5 channels. Key results: A total of 355 compounds were screened for their effects on CT: 32% of these compounds slowed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…Cells were stimulated at 80 BPM with concentrations of flecainide (left panel, 0.5 and 2 μM) (16) and lidocaine (right panel, 5 and 20 μM) corresponding to low and high clinical doses (16). High-dose lidocaine (20 μM) maintained upstroke velocity above 315 V/s, consistent with experiments (27), suggesting that therapeutic lidocaine minimally affects cardiac excitation. Therapeutic flecainide had disparate effects on excitability; 0.5 μM resembled lidocaine, whereas 2 μM substantially reduced upstroke velocity (<285 V/s).…”
Section: Resultssupporting
confidence: 87%
“…Cells were stimulated at 80 BPM with concentrations of flecainide (left panel, 0.5 and 2 μM) (16) and lidocaine (right panel, 5 and 20 μM) corresponding to low and high clinical doses (16). High-dose lidocaine (20 μM) maintained upstroke velocity above 315 V/s, consistent with experiments (27), suggesting that therapeutic lidocaine minimally affects cardiac excitation. Therapeutic flecainide had disparate effects on excitability; 0.5 μM resembled lidocaine, whereas 2 μM substantially reduced upstroke velocity (<285 V/s).…”
Section: Resultssupporting
confidence: 87%
“…We found a 19% and 14% decrease in CV at 2 Hz by 90 µM lidocaine in the longitudinal and transverse directions, respectively (Fig. 8C), which is similar to the reported ~19% increase in conduction time at 1 Hz by 100 µM lidocaine in Langendorff-perfused rabbit hearts [42], although direct comparison of these values is complicated by the different models and pacing rates. Additionally, we found more fractional slowing in the longitudinal direction (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…One report suggested that drugs for which the maximum expected plasma concentration was at least thirtyfold lower than the concentration required to block 50% of sodium current was an acceptable safety margin. 54 However, the blocking potency of drug as a function of voltage or rate was not explicitly considered. Further, animal studies have indicated that the relationship between sodium current recorded in a cardiomyocyte and fast conduction may be dissociated with specific mutations in the channel itself 55 or altered function of proteins such as dystrophin and SAP97 that guide its delivery to specific subdomains in the cell.…”
Section: In Vivo Mechanisms Of Sodium Channel Blocking Drug Actionmentioning
confidence: 99%